Electrochemical and hot corrosion behaviour of annealed AlCoCrFeNi HEA coating over steel - N. Radhika; Niveditha Noble; Adeolu Adesoji Adediran (Scientific Reports, 2024)
Abstract The ability to endure extreme corrosion in challenging environments is reduced in stainless steel. This can be addressed by appropriate surface modification techniques to redefine the surface with the required properties. The characteristics of the atmospheric plasma sprayed AlCoCrFeNi High Entropy Alloy (HEA) on SS316l are presented in this study. The coating characterisation revealed uniform coating with homogeneous deposition of gas-atomized AlCoCrFeNi HEA spanning for 150 µm. The coated substrates were further annealed for 2 h at 400 °C, 550 °C, 700 °C and 850 °C and the annealing at 550 °C offered enhanced microstructure. Annealing the coated sample at 550 °C offered a 46% improvement in microhardness against the uncoated sample post-annealing. The electrochemical corrosion tests showcased improved corrosion resistance after annealing through the formation of a protective oxide layer and the influence of HEA. Hot corrosion tests at 900 °C resulted in 10.1%, 8.49%, and 10.36% improved corrosion resistance for the coated sample annealed at 550 °C than the coated sample pre annealing and 44.09%, 44.25%, and 42.09% than the uncoated sample pre annealing under three salt mixtures respectively. The microstructural analysis examines various corrosion modes and verifies the presence and formation of protective oxide layers.